TATANAN HUKUM DI DUNIA MASA KINI - Katronaldo Pratama; Edy; Fiky; Melly; Sepriana; Singgih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The current global legal order has undergone significant changes due to the influence of globalization, technological advancements, and socio-political changes. Legal systems, which were once limited to national jurisdictions, are now increasingly interconnected within a complex network of international law. This article aims to analyze the dynamics of the global legal order, the challenges faced, and the crucial role of international law in creating stability and justice at the global level. The discussion covers key issues such as human rights protection, technology regulation, international dispute resolution, and the impact of social and economic inequalities on legal systems. Despite efforts to harmonize legal systems across countries, differences in legal interpretation and national interests remain major obstacles in building an inclusive and effective legal order. This article suggests the need for reforming legal systems to be more adaptive and strengthening international cooperation to address the ever-evolving legal challenges. Keywords: Legal order, international law, globalization, human rights, technology.